Kepemimpinan Kepala Sekolah dalam Peningkatan Kinerja Guru di Tsanawiyah Darul Ulum Kubu Raya - M. Jali (CV Putra Publisher, 2023)
The purpose of this study was to describe and analyze the principal's leadership in improving teacher performance at Tsanawiyah Darul Ulum Kubu Raya. This research method uses qualitative methods with the type of case study research. The primary data source consists of school principals. Secondary data sources consist of research journals, books, supporting websites and data relevant to this research. Data collection techniques using; interview, observation, and documentation. Data analysis using categorization analysis means finding meaning relevant to the issues that arise in leadership. Basically, the leadership of the principal at Madrasah Tsanawiyah Darul Ulum performs the main duties of the principal and approaches teachers in a capable way. Principal leadership can result in increased teacher performance due to both internal and external supporting factors, as well as motivation for discipline. In addition, the principal also has efforts to improve teacher performance by providing rewards, meetings once every three months, hospitality, and continuously motivating discipline. Increasing teacher performance itself is because there are supporting factors in carrying out school effectiveness, namely; internal and external supporting factors. While the school's efforts to improve teacher performance are by providing rewards and meeting once every three months.